Ethnobotanical Uses of Plants among the Bhotiya Tribal Communities of Niti Valley in Central Himalaya, India - Phondani, Prakash Chandra; Maikhuri, Rakesh Kumar; Rawat, Lakhpat Singh; Farooquee, Nehal Ahmad; Kala, Chandra Prakash; Vishvakarma, S.C. Ram; Rao, K. S.; Saxena, K. G. (Ethnobotany Research and Applications, 2010)
A study of the medicinal plants and knowledge of diseases was conducted in Bhotiya tribal communities in the Niti valley of Alaknanda catchment in Central Himalaya. Indigenous knowledge of local traditional healers about plants used for medicinal purposes was collected through questionnaire and interviews. Eighty-six plant species were identified as being used for treatment of 37 common ailments. The methods and application of uses of these plants varies and was based on the nature of disease.